Peran Kepuasan Dalam Memediasi Pengaruh E-Word Of Mouth Dan Kualitas Layanan Financial Technology Terhadap Loyalitas Nasabah Bank Syariah - adha, mufti alam (ITB AAS INDONESIA Surakarta, 2024)
This research aims to explore the role of satisfaction as a mediator in connecting the influence of e-Word of Mouth (e-WOM) and Financial Technology (FinTech) service quality on customer loyalty at Islamic Banks in Magelang. The survey method was used to collect data from one hundred Islamic Bank customer respondents in Magelang using a structured questionnaire. Quantitative research methods were used in this research. Multiple regression analysis and mediation analysis with a Sobel test approach will be used to test the relationship between the variables in question. The findings from this research will provide a deeper understanding of the factors that influence customer loyalty in the Islamic banking industry, especially in the digital era. The results of this research are expected to provide better insight into how e-Word of Mouth and Financial Technology service quality contribute to the formation of customer loyalty at Islamic Banks in Magelang, as well as the essential role of satisfaction as a mediator in this relationship. The practical implications of this research can help bank managers improve marketing and service strategies to strengthen customer loyalty, especially in the context of the increasingly developing Islamic banking industry. Apart from that, this research can also be a contribution to the literature on services marketing, especially in understanding the dynamics of interactions between key variables in the context of the Islamic and digital banking industry.